1972
DOI: 10.1002/pssa.2210130238
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-diffraction study of UAsSe and USbSe

Abstract: Neutron‐diffraction study of UAsSe and USbSe, both of PbFCl‐type crystal structure (space group P4/mnm) has been made at 4.2°K and room temperature. The position parameters u and z for uranium and selenium atoms, respectively, were determined for both compounds. Neutron‐diffraction patterns taken at 4.2°K revealed that these compounds have simple uniaxial ferromagnetic structure. The magnetic moment of uranium is aligned along the fourfold crystal axis. Its value is (1.5 ± 0.1) BM, both in UAsSe and USbSe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 8 publications
0
7
1
2
Order By: Relevance
“…This suggestion is also composition UAs supported by a fairly large difference in the corresponding magnetic transition temperatures ( Table 1). On the other hand, J' is expected in all compositions to be fairly constantsuch an assumption i s based on the fact that the environment and geometry of the two ferromagnetically aligned sheets do not differ much, even for the end members UAs2 and UAsSe (12). In the course of the present neutron-diffraction study we observed collinear moment alignment in the whole system.…”
Section: Resultsmentioning
confidence: 53%
“…This suggestion is also composition UAs supported by a fairly large difference in the corresponding magnetic transition temperatures ( Table 1). On the other hand, J' is expected in all compositions to be fairly constantsuch an assumption i s based on the fact that the environment and geometry of the two ferromagnetically aligned sheets do not differ much, even for the end members UAs2 and UAsSe (12). In the course of the present neutron-diffraction study we observed collinear moment alignment in the whole system.…”
Section: Resultsmentioning
confidence: 53%
“…16 In stoichiometric UAsSe, As and Se atoms are located on the different lattice sites and a random distribution of As and Se atoms has been excluded by a neutron scattering experiment. 39 For crystals with variations of the arsenic to selenide ratio some disorder in the anionic sublattice occurs as was indicated by x-ray and neutron diffraction experiments. 40 Angle-resolved photoemission studies were performed at the Synchrotron Radiation Center of the University of Wisconsin in Stoughton.…”
Section: Methods: Experimentsmentioning
confidence: 89%
“…The fact that UAsSe becomes ferromagnetic below T c B110 K [2] initially suggested a scattering mechanism of magnetic origin related to the original Kondo effect [11]. Early investigations thus concentrated on the determination of the low-temperature magnetic structure and its relation to the electronic structure [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since the initial discovery of these unusual low-temperature transport properties in UAsSe, there has been much interest in the Kondo scattering mechanism/s responsible [1][2][3][4][5][6][7][8][9][10]. The fact that UAsSe becomes ferromagnetic below T c B110 K [2] initially suggested a scattering mechanism of magnetic origin related to the original Kondo effect [11].…”
Section: Introductionmentioning
confidence: 99%